2007
DOI: 10.1080/14662040701659910
|View full text |Cite
|
Sign up to set email alerts
|

The Political Economy of Governance Reforms in Uganda

Abstract: About IDSThe Institute of Development Studies is one of the world's leading organisations for research, teaching and communications on international development. Founded in 1966, the Institute enjoys an international reputation based on the quality of its work and the rigour with which it applies academic skills to real world challenges. Its purpose is to understand and explain the world, and to try to change it -to influence as well as to inform.IDS hosts five dynamic research programmes, five popular postgra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 10 publications
0
34
0
Order By: Relevance
“…Local politicians may lack commitment to accounting reforms that erode their power to siphon public funds from government treasuries and extract economic rents within a façade of rules (Cammack, 2007). For example, anti-corruption initiatives in Uganda threatening the regime's patronage-based support lacked political commitment (Robinson, 2006). The failure of IFMS in Ghana was attributed to politicians believing that it was a technical matter foisted on them, but their support waned when they realised the political implications of greater transparency and accountability (Wynne, 2005).…”
Section: Government Accounting and The Resurrection Of The Statementioning
confidence: 99%
“…Local politicians may lack commitment to accounting reforms that erode their power to siphon public funds from government treasuries and extract economic rents within a façade of rules (Cammack, 2007). For example, anti-corruption initiatives in Uganda threatening the regime's patronage-based support lacked political commitment (Robinson, 2006). The failure of IFMS in Ghana was attributed to politicians believing that it was a technical matter foisted on them, but their support waned when they realised the political implications of greater transparency and accountability (Wynne, 2005).…”
Section: Government Accounting and The Resurrection Of The Statementioning
confidence: 99%
“…Moreover, tax collection is emphasised at the expense of other broad-based reforms of tax administration, such as systems of financial management. Finally, in the absence of accountability mechanisms, ARAs can become a 'super entity' that can abuse their taxation powers (Robinson, 2006). The question then is whether the benefits of increased autonomy outweigh the costs (Taliercio, 2003a;Mann, 2004;Kidd and Crandall, 2006).…”
Section: The Promise Of the Ara Modelmentioning
confidence: 98%
“…The URA was once heralded as one of Uganda's few pockets of bureaucratic excellence, shielded from overt political influence and the beneficiary of large-scale donor funding (Robinson, 2006). This reputation had diminished by the early 2000s, and while some observers have suggested that the current leadership has largely turned things around again, Uganda's IGG 2008 National Integrity Survey showed that 77 per cent of households rated the URA as corrupt.…”
Section: Revenue Collectionmentioning
confidence: 99%